Screening Older Adults for Depression: Barriers Across Clinical Discipline Training. Issue 2 (29th May 2019) - Smith, Ronald; Meeks, Suzanne
Abstract: Background and Objectives: Depressed older adults are more likely to be seen in primary care than in specialty mental health settings, but research shows that physicians may not routinely screen for depression. Other clinical disciplines are also in a position to screen for depression, but have not been studied. This study examined barriers to screening older adults for depression, and disciplinary differences in clinical trainees' likelihood of screening. Research Design and Methods: We used a cross-sectional, online survey with experimental manipulation of vignettes. A four-way mixed analysis of variance explored the effects of clinical discipline (between subjects) and time pressure, patient difficulty, and level of symptoms (within subjects) on trainees' likelihood of screening. Results: Participants were 229 trainees in medicine (83), psychology (51), nursing (49), and social work (46). Lower time pressure and greater symptom severity increased likelihood of screening. There was a significant three-way interaction among discipline, patient difficulty, and symptom level that was driven by social work graduate trainees' greater likelihood of screening for depression when there were more symptoms present, which was diminished if the patient was being difficult. There was a two-way interaction between patient difficulty and level of symptoms: more symptoms resulted in increased likelihood of screening, an effect that diminished with greater patient difficulty. Discussion and Implications: The study holds implications for identifying and addressing gaps in education on depression screening to minimize the effects of barriers. Interventions could address education about older adults and depression, including practice-based screening, time management, and behavior management skills.